Successful resuscitation after drowning with severe hypernatraemia and prolonged time to return of spontaneous circulation - Klitgaard, T. L. (Anaesth Rep, 2019)
We describe the successful resuscitation of a 23‐year‐old previously healthy man who had drowned. After prolonged submersion, hypothermia, severe hypernatraemia, a prolonged time to return of spontaneous circulation was possible using a combination of extracorporal life support and early continuous veno‐venous haemofiltration. This combination of clinical circumstances is rarely associated with positive outcomes, but this case demonstrates the utility of extracorporeal life support and haemofiltration in patients drowned in saltwater.